2005
DOI: 10.3801/iafss.fss.8-1023
|View full text |Cite
|
Sign up to set email alerts
|

Formation Of Dioxin During Smoldering Of Cca Treated Wood Char

Abstract: Production of dioxin during the smoldering of wood char containing chromated copper arsenate (CCA) was investigated. Preliminary results are presented for the smoldering of treated wood char at 300 and 400°C, as a function of char loading, smoldering time and inlet oxygen concentrations. PCDF (mainly Cl 4 DF) were the preferred products of smoldering, and the results indicate the dependence of PCDD/F yields on competing formation/dechlorination reactions. Early periods of mass conversion favored PCDD/F formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Copper is a particularly potent catalyst for the formation of polychlorinated dibenzo-p-dioxin and polychlorinated dibenzofurans (PCDD/F). The present authors have demonstrated that combustion of treated wood in fires and in smallscale burners (e.g., heating barrels, combustion ovens) may lead to particularly high levels of PCDD/F both in ash and in gaseous emissions [1][2][3][4]. We have reported that the oxidative pyrolysis of wood treated with copper boron azole (CBA) could produce PCDD/F emissions as high as 7500 pg WHO 98 -TEQ/Nm 3 [2].…”
Section: Introductionmentioning
confidence: 99%
“…Copper is a particularly potent catalyst for the formation of polychlorinated dibenzo-p-dioxin and polychlorinated dibenzofurans (PCDD/F). The present authors have demonstrated that combustion of treated wood in fires and in smallscale burners (e.g., heating barrels, combustion ovens) may lead to particularly high levels of PCDD/F both in ash and in gaseous emissions [1][2][3][4]. We have reported that the oxidative pyrolysis of wood treated with copper boron azole (CBA) could produce PCDD/F emissions as high as 7500 pg WHO 98 -TEQ/Nm 3 [2].…”
Section: Introductionmentioning
confidence: 99%